A Compact Single-Feed Circularly Polarized Microstrip Antenna with Symmetric and Wide-Beamwidth Radiation Pattern. (18th November 2013) - Ye, Xihong; He, Mang; Zhou, Pingyuan; Sun, Houjun
Abstract : A compact single-feed circularly polarized microstrip antenna is proposed to achieve symmetric radiation pattern over a wide range of observation angles. In order to reduce the radiation aperture and consequently broaden the circular polarization (CP) and the half power beamwidth (HPBW) of the antenna, a partially etched superstrate and a conducting cavity are employed in the design. Further, reasonable axial ratio (AR) and impedance bandwidths are realized within the compact structure by using a simple series crossed-slot aperture coupled feeding. As a consequence, the overall dimension of the fabricated prototype is 0.32 λ 0 × 0.32 λ 0 × 0.12 λ 0 at the center operating frequency of 1.56 GHz, and a 3.0% overlapped bandwidth of 10 dB return loss (RL) and 3 dB AR is obtained. Within the bandwidth, symmetric CP radiation pattern over almost the entire upper hemisphere is observed and the HPBW is also increased from 60° to 106°.